Быстрый метод расчета радиационных потоков в пространственно ограниченных средах - Горячев Б. В. Борис Валентинович; Ларионов В. В. Виталий Васильевич; Могильницкий С. Б. Сергей Борисович; Савельев Б. А. (Минск, 1987)
Деп. в ВИНИТИ 17.06.87, № 4395-В87